2019
DOI: 10.1016/s2468-1253(18)30379-0
|View full text |Cite
|
Sign up to set email alerts
|

Place of death and factors associated with hospital death in patients who have died from liver disease in England: a national population-based study

Abstract: need to be explored. There is a dire need for prevention strategies as well as end of life care services to prevent and tackle harms from liver disease. Funding NIHR HS&DR programme, CLAHRC South London Keywords Liver disease; hospital death; cause of death; end of life care; alcoholic liver disease; sepsis; hepatorenal syndrome; alcohol related disorders Research in context Evidence before this study Liver disease is a common cause of mortality, and the number of people who died from liver disease in the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…At the end of life, 61%‐78% of patients with DC and 58% of Medicare beneficiaries with HCC not enrolled in hospice die in the hospital. ( 86 , 87 , 88 , 89 , 90 , 91 ) During these long inpatient stays, greater than 50% of patients with AdvLD receive mechanical ventilation, 16% receive dialysis, and 43% receive a blood transfusion, while 28% of patients with HCC use ICU care at the end of life. ( 90 , 92 ) Quality indicators for end‐of‐life care in patients with AdvLD include 1) adequate control of symptoms (pain and dyspnea) and 2) presence of GOC discussions that clarify surrogate decision makers and assure that care received is consistent with the patient’s goals.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of life, 61%‐78% of patients with DC and 58% of Medicare beneficiaries with HCC not enrolled in hospice die in the hospital. ( 86 , 87 , 88 , 89 , 90 , 91 ) During these long inpatient stays, greater than 50% of patients with AdvLD receive mechanical ventilation, 16% receive dialysis, and 43% receive a blood transfusion, while 28% of patients with HCC use ICU care at the end of life. ( 90 , 92 ) Quality indicators for end‐of‐life care in patients with AdvLD include 1) adequate control of symptoms (pain and dyspnea) and 2) presence of GOC discussions that clarify surrogate decision makers and assure that care received is consistent with the patient’s goals.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, about 70% of the deaths occurred outside hospital. In a real‐world setting, cost saving could be greater as the majority with ESLD would be expected to die in hospital 6,35 . A recent study reported that patients with liver disease were twofold more likely to die in an institution with 15% higher costs ( P < 0.001), compared to those without liver disease 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In a real-world setting, cost saving could be greater as the majority with ESLD would be expected to die in hospital. 6,35 A recent study reported that patients with liver disease were twofold more likely to die in an institution with 15% higher costs (P < 0.001), compared to those without liver disease. 36 Since collection of EQ-5D-5L data were feasible, quality adjusted life years could be calculated in a larger study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCEPOD review only reported “established renal failure at presentation,” but this was highly prevalent at 30% for those dying during admission (vs 66% with codes for acute kidney injury among deaths in our study). A recent study of people who died from liver disease in England identified renal complications as strongly associated with hospital death 29 …”
Section: Discussionmentioning
confidence: 99%